HUBUNGAN PENDIDIKAN DAN PEKERJAAN IBU DENGAN UPAYA PENCEGAHAN ISPA PADA BALITA OLEH IBU YANG BERKUNJUNG KE PUSKESMAS KELAYAN TIMUR KOTA BANJARMASIN - Chandra Chandra (An-Nadaa: Jurnal Kesehatan Masyarakat (e-Journal), 2017)
ARTI is a disease that often occurs in children, because the child's body's defence system are still low. ARTI case in the East Kelayan public health center in 2013 found URTI as many as 4673 cases and in 2014 increased to 5067. This study aims to analyze the determinants prevention effort of URTI in toddler in Banjarmasin East Kelayan public health center. Research is an analytic survey with cross sectional approach. The total sample of 144 respondents was taken by accidental sampling. Data were collected using a questionnaire that was tested previously, data collected were analyzed using univariate statistics, bivariate, with chi square test and multivariate analysis with multiple logistic regression analysis. As a result found that respondents who do not take steps to prevent upper respiratory tract infection with either the percentage is greater than the good prevention efforts (67.4% versus 32.6%). Variables significantly associated with the prevention of URTI in toddler (p <0.05) is the mother's age, education and employment. Advice given to PHC of Banjarmasin city East Kelayan, should improve health education for mothers who have children through health promotion services at the public health center.